Exploring the Formulation and Approaches of Injectable Hydrogels Utilizing Hyaluronic Acid in Biomedical Uses - Hadeia Mashaqbeh; Batool Al-Ghzawi; Fatima BaniAmer (Advances in Pharmacological and Pharmaceutical Sciences)
The characteristics of injectable hydrogels make them a prime contender for various biomedical applications. Hyaluronic acid is an essential component of the matrix surrounding the cells; moreover, hyaluronic acid’s structural and biochemical characteristics entice researchers to develop injectable hydrogels for various applications. However, due to its poor mechanical properties, several strategies are used to produce injectable hyaluronic acid hydrogel. This review summarizes published studies on the production of injectable hydrogels based on hyaluronic acid polysaccharide polymers and the biomedical field’s applications for these hydrogel systems. Hyaluronic acid-based hydrogels are divided into two categories based on their injectability mechanisms: in situ-forming​ injectable hydrogels and shear-thinning injectable hydrogels. Many crosslinking methods are used to create injectable hydrogels; chemical crosslinking techniques are the most frequently investigated technique. Hybrid injectable hydrogel systems are widely investigated by blending hyaluronic acid with other polymers or nanoparticulate systems. Injectable hyaluronic acid hydrogels were thoroughly investigated and proven to demonstrate potential in various medical fields, including delivering drugs and cells, tissue repair, and wound dressings.